The Treatment of Anxiety in Young Children: Results of an Open Trial of the Fun FRIENDS Program. Issue 4 (18th September 2015) - Barrett, Paula; Fisak, Brian; Cooper, Marita
Abstract : Background: Preschool-aged children exhibit a relatively high prevalence rate of anxiety disorders, and the course of these disorders is often chronic. However, surprisingly few studies have focused on the treatment of anxiety in this age group. In response to this limitation, the purpose of the current study was to examine the effectiveness of an open trial of the Fun FRIENDS (FF) program, a downward extension of the FRIENDS programs for preschool-aged children (5–7 years), in a community clinic setting. Method: The sample included 31 children diagnosed with an anxiety disorder. Treatment consisted of 10 weekly sessions administered in a group format. Parents also received two information sessions. Child anxiety, behavioural inhibition, and resiliency were assessed at preintervention, immediate postintervention, and at 12-month follow-up. Results: Significant decreases in child anxiety and shyness and improvements on measures of resiliency were observed following the completion of treatment. Conclusions: The results of this study provide support for the effectiveness of the Fun FRIENDS program as a treatment for anxiety in young children. Further, this study adds to the relatively small body of research focused on the use of CBT to treat anxiety disorders in this population.